Anti-inflammatory Therapy for Coronary Atherosclerotic Heart Disease: Unanswered Questions Behind Existing Successes - Ma, Jun; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2021)
Coronary atherosclerotic heart disease is a serious threat to human health. The results of the CANTOS study published in 2017 put an end to the perennial debate about anti-inflammatory treatment of coronary atherosclerotic heart disease. In addition to interleukin 1β monoclonal antibody, interleukin 6 receptor antagonists and colchicine have also shown exciting results in clinical trials within the last three years. However, behind these successes, questions remain that need to be addressed. In this review, we summarize the successes and existing doubts of interleukin 1β antibodies, interleukin 6 receptor antagonists, and colchicine in the anti-inflammatory treatment of coronary atherosclerotic heart disease